RANCANG BANGUN APLIKASI RESTORAN BERBASIS ANDROID 10 MENGGUNAKAN KODULAR DAN FIREBASE APPS DEVELOPER - Hidayat, Atep; Megasyah, Yoga; Wahyudiansyah, Erik (Jurnal Sistem Informasi Galuh, 2026)
The research focuses on the Design and Construction of Android 10 Based Restaurant Application Using Kodular and Firebase Apps. The rapid growth of the restaurant industry and the significant role of Android technology serve as the background. Identified issues include order management, sales report recording, and customer service. The research aims to enhance operational efficiency, reduce errors, and establish an integrated data management system. The methodology encompasses field studies, literature reviews, and the implementation of the Rational Unified Process (RUP) Architecture. The focus is on technical, managerial, and customer experience aspects.